Mesenchymal Stem Cells-Conditioned Medium; An Effective Cell-Free Therapeutic Option for in vitro Maturation of Oocytes - Pour, Fatemeh K.; Gale Dari, Mahrokh Abouali; Ramazii, Mohammad; Keivan, Mona; Farzaneh, Maryam (Current Stem Cell Research & Therapy, 2024)
Infertility is a major reproductive health issue worldwide. One of the main problems in infertile women is the failure to generate or release a mature egg. Therefore, the development of new technologies for in vitro generation or induction of mature oocytes can improve various ART procedures. Recently, stem cell-based therapy has opened a new window for several pathological complications. Mesenchymal stem cells (MSCs) are multipotent stem cells with the capacity to self-renew and differentiate into the mesodermal lineage. MSCs contain various bioactive molecules which are involved in the regulation of key biological processes. They can secret multiple paracrine factors, such as VEGF, IGF, HGF, EGF, and FGF to stimulate egg maturation. Although MSCs represent a promising source for cell therapy, the potential risk of tumor development reduces their clinical applications. Recent studies have suggested that the supernatant or conditioned medium of MSCs also contains similar components and regulates the oocyte behavior. The MSC-conditioned medium can eliminate the safety concerns associated with MSC transplantation and avoid rejection problems. Although MSC and MSC-CM could improve oocyte quality, ovarian function, and fertility, these improvements have not yet been demonstrated in clinical trials in humans. Hereby, we summarized recent research findings of MSCs-derived conditioned medium in in vitro development of immature oocytes.
Keywords: oocytes